EFL Sophomores’ Perspectives on Integrating Intercultural Competence in Language Learning in the KRI Universities - Zina Adil Ismail Chaqmaqchee; Himdad Abdulqahhar Muhammad (Zanco Journal of Human Sciences, 2026)
This study explores intercultural competence from the perspective of learners in the Kurdistan Region of Iraq at public and private universities. The main goal was to identify students’ perceptions and the challenges in an educational field in both universities, with a focus on diverse cultural contexts. The research further highlights the importance of intercultural competence in enhancing EFL professional development. Seventy sophomores from the public university and thirty-three students of the same level from the private university participated in the study. A descriptive research design employing both quantitative and qualitative methods was adopted. Questionnaire and classroom observations served as the primary tools for the secondary source data collection. Descriptive analysis, including an independent t-test, was used to compare findings between the two types of universities. Qualitative thematic analysis was applied as a narrative process to interpret the collected data. The results indicated that students at the public university obtained a mean score of 3.47 demonstrating a higher level than the private university’s estimated score of 3.36, having a slightly lower percentage. Thus, the results for both universities were below p<0.05, and there were no statistical differences between them on the tested variable; nevertheless, the findings are significant. Generally, the results revealed positive perceptions from students towards intercultural competence, although they faced challenges in the learning process based on the analysis of classroom observations.